2010
DOI: 10.1038/hr.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase inhibitor prevents ischemic brain damage via reduction of vasogenic edema

Abstract: Release of neutrophil elastase is one of the harmful inflammatory reactions in acute cerebral ischemia. Therefore, inhibition of elastase released from neutrophils could be a useful strategy for the treatment of acute stroke. To evaluate this hypothesis, the effect of sivelestat, a selective neutrophil elastase inhibitor was examined in a mouse model of focal ischemia. The results obtained indicate that sivelestat reduced brain edema and vascular permeability, and subsequently improved the neurological deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 29 publications
1
38
0
Order By: Relevance
“…Neutrophils, and neutrophil-derived NE in particular, have been implicated in edema formation in the ischemic brain (Stowe et al, 2009; Ikegame et al, 2010). We therefore examined the effect of genetic deficiency of NE on vasogenic edema in the immature injured brain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neutrophils, and neutrophil-derived NE in particular, have been implicated in edema formation in the ischemic brain (Stowe et al, 2009; Ikegame et al, 2010). We therefore examined the effect of genetic deficiency of NE on vasogenic edema in the immature injured brain.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with our results, treatment with the same NE inhibitor at 0 and 4 h during reperfusion after transient middle cerebral artery occlusion in mice reduced infarct volume, BBB disruption and edema by 24 h (Stowe et al, 2009). Other inhibitors of NE (ONO-5046 or sivelestat) have also shown efficacy at reducing neuronal loss, edema and vascular permeability after focal ischemia in rats or rabbits (Shimakura et al, 2000; Matayoshi et al, 2009; Ikegame et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is supported by findings in pharmacologic and transgenic mice models of neutrophil inhibition. 40,41 In a therapeutic setting, neutralization of IL-17A even 3 hours after stroke resulted in diminished neutrophil infiltration and in a better neurologic outcome in mice. Thus, IL-17A provides an ideal target because its main appearance in stroke is short-lived and has, to our knowledge, only proinflammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Using an in vitro model of BBB (Weksler et al 2005), we have recently reported that HDLs could limit the deleterious, elastase-mediated role of activated neutrophils under oxygen-glucose deprivation conditions leading to BBB disruption (Bao . In stroke, inhibition of neutrophil elastase may be a therapeutic target, as shown by using specific inhibitors (Ikegame et al 2010). …”
Section: Anti-inflammatory and Antiprotease Propertiesmentioning
confidence: 99%